2005
DOI: 10.1172/jci23219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the PPARγ agonist pioglitazone on lipoprotein metabolism in patients with type 2 diabetes mellitus

Abstract: Elevated plasma levels of VLDL triglycerides (TGs) are characteristic of patients with type 2 diabetes mellitus (T2DM) and are associated with increased production rates (PRs) of VLDL TGs and apoB. Lipoprotein lipase-mediated (LPL-mediated) lipolysis of VLDL TGs may also be reduced in T2DM if the level of LPL is decreased and/or the level of plasma apoC-III, an inhibitor of LPL-mediated lipolysis, is increased. We studied the effects of pioglitazone (Pio), a PPARγ agonist that improves insulin sensitivity, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
88
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 108 publications
(101 reference statements)
7
88
1
1
Order By: Relevance
“…These results are consistent with the concept that the insulin-sensitising effect of PPAR-γ agonists, at least in part, are indirect and mediated via a reduction in plasma NEFA and intramyocellular concentration of toxic lipid metabolites [1,35]. In a recent study [36], PIO was shown to enhance the clearance of very-low-density-lipoprotein (VLDL) triacylglycerol-rich particles from the circulation. However, since substrate (plasma NEFA and glucose) delivery to the liver plays an important role in hepatic triacylglycerol synthesis [37], one could hypothesise that part of PIO's triacylglycerol-lowering effect could be related to the reduction in plasma NEFA and/or glucose concentrations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with the concept that the insulin-sensitising effect of PPAR-γ agonists, at least in part, are indirect and mediated via a reduction in plasma NEFA and intramyocellular concentration of toxic lipid metabolites [1,35]. In a recent study [36], PIO was shown to enhance the clearance of very-low-density-lipoprotein (VLDL) triacylglycerol-rich particles from the circulation. However, since substrate (plasma NEFA and glucose) delivery to the liver plays an important role in hepatic triacylglycerol synthesis [37], one could hypothesise that part of PIO's triacylglycerol-lowering effect could be related to the reduction in plasma NEFA and/or glucose concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, PIO does not alter APOA5 expression in patients with type 2 diabetes [36]. Despite the widespread use of PPAR-α agonists (i.e.…”
Section: Discussionmentioning
confidence: 93%
“…Apolipoprotein C-III is an inhibitor of LPL and its absence is known to accelerate the disposal of dietary lipid [35]. A recent study on the effect of treatment with pioglitazone in a group of eight type 2 diabetic patients has shown a decrease in apolipoprotein C-III levels, although this is not thought to be mediated through the PPAR-γ receptor [36]. Some influence of insulin resistance on C-III levels can be inferred from the finding that its concentration in plasma correlates strongly with the level of production and concentration of VLDL triglyceride and also with the HOMA score of insulin sensitivity [37].…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic humans, pioglitazone lowers triglycerides by increasing clearance of very low‐density lipoproteins (VLDL), ostensibly through enhanced activity of lipoprotein lipase, an insulin‐regulated enzyme that mediates VLDL‐triglyceride hydrolysis 29. A similar mechanism may have been responsible for the decrease in triglycerides in the obese cats.…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism may have been responsible for the decrease in triglycerides in the obese cats. With regard to cholesterol, the effects of pioglitazone differ between humans and cats: pioglitazone increases high‐density lipoprotein (HDL) cholesterol in humans, but does not affect total cholesterol 20, 29. This difference may relate to the fact that (1) cats carry most of their cholesterol in HDL, and (2) activity of cholesteryl ester transfer protein, which catalyzes the exchange of cholesterol between HDL and other lipoproteins, appears to be very low in cats 30.…”
Section: Discussionmentioning
confidence: 99%